2023
DOI: 10.1155/2023/2894552
|View full text |Cite
|
Sign up to set email alerts
|

Care Transitions for People with Acquired Neurological Disability in the First 12 Months following Inpatient Rehabilitation: Health Service Use and Obstacles

Yanfei Xie,
Mandy Nielsen,
Melissa Kendall
et al.

Abstract: Due to their complex and fluctuating needs requiring multiple transitions of care through different services and systems, the early postdischarge period is one of the vulnerabilities for people with acquired neurological disability. This study aimed to (1) map and examine system-level care transitions, including change in transition patterns and service use among people with acquired neurological disability during the first 12 months postdischarge and (2) explore the relationship between early perceptions (3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Xie et al [6] identified that individuals with acquired neurological disability experienced, on average, eight care transitions in the first 12 months postdischarge. Care transitions are known points of vulnerability for people with ABI due to their diverse and complex support needs [2].…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al [6] identified that individuals with acquired neurological disability experienced, on average, eight care transitions in the first 12 months postdischarge. Care transitions are known points of vulnerability for people with ABI due to their diverse and complex support needs [2].…”
Section: Introductionmentioning
confidence: 99%